2011
DOI: 10.1021/ol200940a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed [3 + 2] Annulations of γ-Functionalized Butynoates and 1C,3O-Bisnucleophiles: Highly Selective Reagent-Controlled Pathways to Polysubstituted Furans

Abstract: In this paper, a reagent-controlled [3+2] annulation of γ-functionalized butynoates 1 and 1C,3O-bisnucleophiles 2 is reported, which leads to three distinct furan skeletons 3-5. A PPh(3) catalyst preferentially attached the β-position of 1a, facilitating α-addition to furnish Type I annulations. With the assistance of Ag(2)O, Type II annulations were achieved via selective γ-substitution. In the absence of the PPh(3) catalyst, the reagent Cs(2)CO(3) promoted β-addition to realize Type III annulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…In 2011, Tong reported the first example of phosphine-catalyzed furan synthesis from an alkynoate and a carbon pronucleophile. 518 In Tong’s proposed mechanism, addition of triphenylphosphine generates the familiar vinyl phosphonium enoate 292 , which further activates the pronucleophile 293 through deprotonation (Scheme 447). Subsequent net α -umpolung addition, accompanied by the loss of acetate, gives the intermediate 294 .…”
Section: Nucleophilic Phosphine Catalysis Of Acetylenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Tong reported the first example of phosphine-catalyzed furan synthesis from an alkynoate and a carbon pronucleophile. 518 In Tong’s proposed mechanism, addition of triphenylphosphine generates the familiar vinyl phosphonium enoate 292 , which further activates the pronucleophile 293 through deprotonation (Scheme 447). Subsequent net α -umpolung addition, accompanied by the loss of acetate, gives the intermediate 294 .…”
Section: Nucleophilic Phosphine Catalysis Of Acetylenesmentioning
confidence: 99%
“…Tong demonstrated that functionalized trisubstituted furans could be constructed through an alternative route (Scheme 449). 518 From methyl 4-bromo-2-butynoate, similar activation of the carbon pronucleophile occurs to generate the ion pair 298 . Upon coordination with a silver salt, formal γ -umpolung addition occurs to afford the intermediate 299 .…”
Section: Nucleophilic Phosphine Catalysis Of Acetylenesmentioning
confidence: 99%
“…91 Later, Tong's group has reported the synthesis of polysubstituted furans following similar strategies to those aforementioned, from g-functionalized butynoates and 1,3-dicarbonyl compounds, catalyzed by triphenylphosphine. 92 The authors were able to control the substitution pattern by reagent-controlled pathways. Thus, when the leaving group in the alkyne was an acetoxy group (173), the annulation leaded to a furan by an initial a-addition followed by a Michael reaction (left-Scheme 77).…”
Section: Reactions Of Alkynes With Di-nucleophilesmentioning
confidence: 99%
“…In 2003, Zhu et al firstly reported the [4 + 2] annulation reaction of allenoates and N-tosylbenzaldimines to form functionalized tetrahydropyridines [25], which leads to the large-scale applications of the phosphinecatalysts. Since the pioneer work of Lu and Kwon are reported, many efforts have been devoted to improve and develop various kinds of the phosphine-catalyzed reactions [2,12,[26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In 2009, Kwon reported phosphine-catalyzed [3 + 3] annulations of aziridines and allenoates to get azidirines in room temperature [40].…”
Section: Introductionmentioning
confidence: 99%